The Alzheimer's prevention initiative Generation program: A global perspective on best practices for site support and engagement to accelerate participant recruitment: Clinical trial design and implementation. (7th December 2020) - Walsh, Trisha L.; Riviere, Marie‐Emmanuelle; Tariot, Pierre N.; Alred, Melody; Doak, Karen; Liu, Fonda; Ricart, Javier; Scholten, Ingo; Arbuckle, Julian; Quinn, Matt; Duff, Laurie; Smith, Molly; et al.
Abstract: Background: The API Generation Program consists of two trials: Generation Studies 1 and 2. Generation Study 1 enrolled cognitively unimpaired APOE4 homozygotes (HMs) ages 60‐75; Generation Study 2 enrolled cognitively unimpaired APOE4 carriers (HMs and heterozygotes (HTs), HTs had to have elevated brain amyloid). To address the unique challenges with recruitment of this population, we developed a multifaceted approach to maintaining engagement with sites and sharing best practices for recruitment among study site teams. Method: We designed a flexible menu of novel recruitment tactics and implemented strategies, some of which were country‐specific, and collaborated with site teams on a regular basis. We conducted individualized "recruitment planning and implementation" calls with sites soon after they were activated, traveled to sites for in‐person meetings, held regional and country‐wide workshops and roundtable meetings, bi‐monthly study coordinator calls, and monthly media training calls. In addition, we developed an online recruitment and retention toolkit to provide a one‐stop shop for sites to review available, IRB approved materials that could be ordered and customized to meet their site‐specific needs. In the US, we consulted with UsA2 for cultural competency to develop a tip sheet for minority community engagement, postcards, ads, and brochures specific to the Latino and African American communities near study sites. Result: Recruitment was terminated in July 2019 after an early signal of mild worsening in some measures of cognitive function with umibecestat. At the time the program closed, 35, 333 participants had come to a study site for genetic testing, 9, 623 screened and 1, 626 were randomized. 50% of activated sites had enrolled at least five participants between both studies. Despite the unprecedented challenges for recruitment of cognitively normal APOE4 HMs and HTs, we were on target to complete enrollment by end of 2019. Results from specific engagement and recruitment strategies, along with characteristics of high enrolling sites, will be presented. Conclusion: Collaboration between study sponsor and site teams and the development of flexible recruitment plans and materials that can be adapted to meet sites' needs played a crucial role in the successful recruitment, enrollment, and retention of participants for the API Generation Program.